Peningkatan Kemampuan Siswa Menulis Bahasa Inggris Narrative Text dengan Media Gambar Berseri - Hetty Dwi Agustin (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2013)
In the classroom, students often complain and say it is difficult if the teacher give them the task to write in English. The students would say they could not do it even when they haven’t  begun yet. They do not have self-confident, feeling afraid of doing wrong, do not know what to write and how to get started. For those reasons the teacher conduct Class Action Research using images Pinocchio and Cinderella as a medium of teaching on learning to write Narrative Text. The results showed that the use of images media is able to increase the students’ ability to write narrative text in English class VIII-F. For increasing the students’ excitement in gaining an idea of writing a story narrative, the authors advise teachers to use images in the form of picture books, comic books, or comic strips, newspaper story as a source of inspiration.